Ethnomathematics Textbook Material on Geometry and Measurement in Elementary Schools - Amilia Suganda, Vina; Pramutia, Zahra; Harini, Bunda; Cahaya Nurani, Dwi; Leva Okta Safitri, Mazda; Lestari, Putri; Chaniago, Farizki (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Ethnomathematics learning is considered to be able to improve the reasoning power of elementary school level students because ethnomathematics learning describes all the things that form the cultural identity of a group which will stimulate students' reasoning power because with ethnomathematics it is easier for students to remember the essential characteristics of an object to be studied. Mathematical material that is presented by relating to the culture in the area where students live will be easier for students to understand. This is a consideration for researchers to use the Ethnomathematics approach which is presented in the form of a textbook. The results of this research obtained an Ethnomathematics-based textbook with a percentage of 94.16% in the Very Valid category. Next, in the trial stage, an average score of 96.10% was obtained from 12 class V students at SD Negeri 24 Pagar Alam in the very practical category.